Effect of a single breeding season on the reproductive performance of beef cattle - Cubas, Antonio Carlos; Lesskiu, Carlos; Tahira, José Kazumassa; Mancio, Antonio Bento (Pesquisa Agropecuaria Brasileira, 2014)
The reproductive performance of 47 half-blood Canchim cows, systematically exposed to a breeding season from October 1st through January 31st was studied with a bull/cow ratio of 1/23. Birth rate obtained during the three years (1979 - 1981) was 61,7%. Year was a significant (P
Keywords: birth season; fertility